Considerations for Direct Land Application of Organic Waste Products - Eberle, William M. (My University, 1997)
This publication explains the application of organic waste products and the considerations for direct land application.
MF2274_1997_08
Keywords: MF2274; Environment and Natural Resources; Equipment and structures; MF